Analisis Sistem Informasi Akuntansi PenjualanTunai Pada PT Garam Pintar Asia - Bhoko, Maria Aloysia; Dince, Maria Nona; Lamawitak , Paulus Libu (Universitas Nusa Nipa Maumere, 2025)
This research animed to analyze the cash sales accounting information system at PT Garam Pintar Asia.The research method employed was descripitive qualitative since the data collected consisted of statements obtained by the resear cher. The data collection techniques used in this study were interviews, observations, and documentation.The sources of data consistend of both primary and secondary data. The result of this study indicated that the cash sales accounting information system implemented by PT Garam Pintar Asia was still not effective. This was evident in the absence of a clear separation of duties for functions related to cash sales, with the cashier concurrently handling cash and accounting functions. The documentation employed within the cash sales accounting information system did not conform to established accounting standards, as the company had yet to implement formal cash sales invoices and cash register receipts, relying instead on simple handwritten notes as evidence of payment. Furthermore, the company had not designed a cash sales flowchart and did not yet have a financial application to manage cash sales transactions.Instead, Microsoft Excel was used merely to record cash sales transactions, proofs of transactions, and sales reports.